Dispositifs pédagogiques dans l'enseignement supérieur et insertion des diplômés - Thierry Chevallier; Jean-François Giret
This paper studies the effects of higher education teaching and learning practices on the early careers of graduates. It draws on data from a quantitative survey conducted with 11'000 graduates in five European countries and in Japan, five years after graduation. Analysing answers related to the organisation of studies revealed four "pedagogical models": 1) the traditional academic model, 2) the research-based model, 3) a semi-professional model and 4) a pure professional model. It appears that there is a strong link between education and employment for graduates from programmes classified as professional, whilst research-based programmes are assessed as enabling students to develop higher order skills.